KONTRIBUSI HASIL BELAJAR PRODUK KREATIF DAN KEWIRAUSAHAAN TERHADAP MINAT WIRAUSAHA SISWA - Yuni, Annisa Rahma; Yulastri, Asmar; Gusnita, Wiwik; Indrayeni, Wiwik (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: This research is motivated by the low entrepreneurial interest of students at SMKN 1 Ampek Angkek after graduation, although the main objective of vocational schools is to prepare students to enter the industrial world, continue their education, and become independent entrepreneurs. The subject of Creative Products and Entrepreneurship (PKK) is expected to support these objectives; however, the reality shows that even though PKK scores are relatively high, students’ entrepreneurial interest remains low. This study aims to describe students’ PKK learning outcomes, describe their entrepreneurial interest, and analyze the influence of PKK learning outcomes on students’ entrepreneurial interest. The method used is quantitative descriptive with a correlational approach. The population consists of 284 eleventh-grade students of SMKN 1 Ampek Angkek, while the sample size was determined using the Slovin formula, resulting in 74 students selected through proportional random sampling. The research instrument was a five-point Likert scale questionnaire that had been tested for validity and reliability. Data analysis employed the t-test. The results showed that PKK learning outcomes were in the good category, while entrepreneurial interest was in the moderate category. The t-test produced a p-value of 0.276 > 0.05, indicating that H₀ is accepted and Hₐ is rejected. The coefficient of determination (R Square) of 0.016 indicates that PKK learning outcomes only contribute 1.6% to students’ entrepreneurial interest.Keywords: Learning Outcomes, Entrepreneurial Interest, Vocational School, Creative Products and Entrepreneurship, Student Entrepreneurship.